Educational effects of widening access to the academic track: a natural experiment - Eric Maurin; Sandra McNally (Institute for the Study of Labor (IZA), 2007)
It is difficult to know whether widening access to schools which provide a more academically oriented general education makes a difference to average educational achievement. We make use of reforms affecting admission to the 'high ability' track in Northern Ireland, but not England. The comparison of educational outcomes between Northern Ireland and England before and after the reform identifies the net effect of expanding the academic track to accommodate more students. This is composed of the direct effect of the more academic track on individual performance and the indirect effect arising on account of the change in peer group composition. Our paper is relevant to debate on the consequences of ability tracking and of expanding access to the academic track
urn:nbn:de:101:1-20080422244
Keywords: 330; Allgemeinbildende Schule; Hochschule; Bildungschancen; Bildungsniveau; Bildungsreform; Vergleich; Nordirland; England